2022
DOI: 10.1002/cne.25406
|View full text |Cite
|
Sign up to set email alerts
|

Tonotopic differentiation of presynaptic neurotransmitter‐releasing machinery in the auditory brainstem during the prehearing period and its selective deficits in Fmr1 knockout mice

Abstract: Tonotopic organization is a fundamental feature of the auditory system. In the developing auditory brainstem, the ontogeny and maturation of neurotransmission progress from high to low frequencies along the tonotopic axis. To explore the underlying mechanism of this tonotopic development, we aim to determine whether the presynaptic machinery responsible for neurotransmitter release is tonotopically differentiated during development. In the current study, we examined vesicular neurotransmitter transporters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 138 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…It has been outlined that the molecular cause of FXTAS is the presence of a PM ranged (55–200 units) expansion of the CGG short-tandem-repeat (STR) locus located within the 5′-UTR of the FMR1 gene [ 7 ]. In recent years, several other neurodegenerative disorders have been associated with a PM ranged CGG STR expansion as their genetic cause [ 193 , 194 , 195 , 196 , 197 ]. These diseases include neuronal intranuclear inclusion disease (NIID), oculopharyngodistal myopathy (OPDM), and oculopharyngeal myopathy with leukoencephalopathy (OPML).…”
Section: The Molecular Basis Of Fxpacmentioning
confidence: 99%
“…It has been outlined that the molecular cause of FXTAS is the presence of a PM ranged (55–200 units) expansion of the CGG short-tandem-repeat (STR) locus located within the 5′-UTR of the FMR1 gene [ 7 ]. In recent years, several other neurodegenerative disorders have been associated with a PM ranged CGG STR expansion as their genetic cause [ 193 , 194 , 195 , 196 , 197 ]. These diseases include neuronal intranuclear inclusion disease (NIID), oculopharyngodistal myopathy (OPDM), and oculopharyngeal myopathy with leukoencephalopathy (OPML).…”
Section: The Molecular Basis Of Fxpacmentioning
confidence: 99%
“…Thus, PNs of the MNTB receive glycinergic and/or GABAergic inhibitory inputs from the ipsilateral ventral nucleus of the trapezoid body (VNTB) and the MNTB itself (Kuwabara et al, 1991 ; Albrecht et al, 2014 ; Dondzillo et al, 2016 ) and excitatory cholinergic input from the superior olivary nuclei (Zhang et al, 2021 ). Since a higher expression level of GAD-67 (McCullagh et al, 2017 ), GABA vesicular transporter (VGAT; Yu and Wang, 2022 ), and glycine transporter 2 (GlyT2; McCullagh et al, 2017 ) is observed in the lateral side of the MNTB, one can propose that the increased number of non-calyceal inputs in the medial region could arise from the cholinergic innervation. However, based on the lack of sufficient knowledge, an increase of other neuromodulatory inputs cannot be precluded.…”
Section: Discussionmentioning
confidence: 99%
“…This temporary developmental gradient along the tonotopic axis is established during the critical period before the hearing onset (P12–P14). Considering that calyceal competition occurs during the same developmental windows (Rodríguez-Contreras et al, 2008 ; Sierksma et al, 2020 ) and that the maturation of neurotransmission progresses from high to low frequencies along the tonotopic axis (Yu and Wang, 2022 ), one can speculate that the only plastic window for eliminating terminals is during the critical period. Since low frequencies mature later, one can consider that not all MNTB cells located in this region mature before the end of the critical period, leaving an incomplete elimination of its calyceal inputs.…”
Section: Discussionmentioning
confidence: 99%